From Guardian of the Constitution to Interpreter of Social Justice: An Analysis of the Post-Reform Role of the Constitutional Court and the Threat of Its Politicization - Michael Chandra O; Ehri Ehri; Winson Winson (Journal of Social Research, 2025)
The birth of the post-reform Constitutional Court (MK) is often narrowly interpreted by the public as that of "Election Calculators" or guardians of constitutional procedures. This view overlooks the historical mandate of its establishment, namely as an antithesis to the failure to fulfill social justice during the New Order era. This research aims to show that the Constitutional Court’s most critical role is not that of a passive constitutional guardian but rather that of an active interpreter and enforcer of social justice. The study uses normative legal research methods with a qualitative-philosophical approach. The argument is constructed using the structure of a "three-act drama”: (1) exposing the status quo of the New Order legacy and the narrow view of the role of the Constitutional Court; (2) conducting a confrontation by analyzing four landmark decisions of the Constitutional Court (case studies of the Water Resources Law, the Job Creation Law, Streams of Trust, and PHPU 2019) as evidence of its role in interpreting substantive and procedural justice; (3) offering a resolution in the form of an analysis of the threat of politicization to this crucial role. The results show that the Constitutional Court has consistently expanded its role from judicial-procedural to judicial-substantive. Ironically, however, this role as an interpreter of social justice is now threatened by political intervention, an echo of the past that reform seeks to eradicate.